Dermatological conditions presenting at the Emergency Department in Siena University Hospital from 2006 to 2011. (22nd April 2014) - Rubegni, P.; Cevenini, G.; Lamberti, A.; Bruni, F.; Tiezzi, R.; Verzuri, A.; Barbini, P.; Manzi, P.; Fimiani, M.
Abstract Background Published studies on emergency dermatology consultations are few because there are few dermatology emergency units in the world. No study has yet described the Italian situation. Objectives To quantify and characterize patients evaluated in our dermatology emergency unit from 2006 to 2011. Methods We studied personal details, diagnosis, annual trend of cases, emergency level and hospitalization of dermatology cases over the 6‐year period. Results A total of 12 226 patients were evaluated. The most numerous diagnostic group was infections (27.1%), followed by non‐specific and descriptive diagnosis (22.5%), skin conditions caused by mechanical or physical agents (13.1%), eczematous diseases (10.5%), insect bites (9.5%) and urticaria/angio‐oedema (8.8%). The most common indications for admission to hospital were skin conditions caused by mechanical or physical agents (33.3%), infections (27.5%), drug eruption (15.9%) and autoimmune or inflammatory disorders (7.4%). Emergency dermatology cases followed a variable annual trend, with more consultations in the summer months. Conclusion This is the first long‐term retrospective analysis of a large series of dermatology emergency patients. It provides useful quantitative and qualitative information on cases for physicians and the national health system for the purposes of improving patient care and cost‐effectiveness.